An optimum of the assignment problem in choosing internship companies among STML students - Mat Isa, Siti Mariam; Abdul Rahim, Mohd Kamarul Irwan (Universiti Utara Malaysia, 2020)
In this research, a mathematical model programming using an AMPL (A Mathematical Programming Language) software is presented to help the administrators with the assigning process. The goal of the optimization model is to ensure equality among students while at the same time trying to grant their wishes to do their internship at companies they preferred. An unfair division of companies can cause frustration among students. Therefore, it is important that the preferences of the students are met in the best way possible. The results show that mathematical programming model can be used to assign students to companies for internship based on their preferences.